Political Role of Nursing in kingdom of Bahrain - Hasani, Faten (International Journal For Research In Health Sciences And Nursing, 2021)
Women in Bahrain have not historically been given equal rights to their male counterparts (Wang, Lindenfors, Sundström, Jansson, & Lindberg, 2012). While recent decades have seen an increase in the areas in which equality for females is being improved, such initiatives have not reached the level of ensuring the ability of women to contribute meaningfully to the Bahraini community outside of the home (Moghadam, 2016). This has created a situation in which women, even those with high levels of education, are unable to fully reach their potential to have meaningful impact on the country (Moghadam, Explaining divergent outcomes of the Arab Spring: The significance of gender and women’s mobilizations, 2016).This is particularly true in the area of nursing, where women have traditionally been able to pursue education and find meaningful employment in both healthcare and child care. Bahraini women have pursued educational opportunities in nursing, some as far as earning advanced degrees, and have been able to work up to management roles in the nursing community (Hatem, 2018). This has, however, generally been the extent of the ability of a woman to grow in her professional role.